2009
DOI: 10.1002/pro.278
|View full text |Cite
|
Sign up to set email alerts
|

HOP is a monomer: Investigation of the oligomeric state of the co‐chaperone HOP

Abstract: The co-chaperone Hsp70-Hsp90 organizing protein (HOP) plays a central role in protein folding in vivo, binding to both Hsp70 and Hsp90 and bringing them together in a functional complex. Reports in the literature concerning the oligomeric state of HOP have been inconsistent-is it a monomer, dimer, or higher order oligomer? Knowing the oligomeric state of HOP is important, because it places limits on the number and types of multiprotein complexes that can form during the folding cycle. Thus, the number of feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
6
19
0
Order By: Relevance
“…4b). Release of the TPR1-DP1 module from the Hsp90:Hop complex core could allow Hsp90 and Hop interaction with other chaperones or co-chaperones, in accordance with other studies 14,27 . The arrangement of the Hop domains in the complex seems to prevent total closure of the Hsp90 dimer, thus blocking ATPase activity and generating a semiclosed conformation that allows client protein binding 16,27,28 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…4b). Release of the TPR1-DP1 module from the Hsp90:Hop complex core could allow Hsp90 and Hop interaction with other chaperones or co-chaperones, in accordance with other studies 14,27 . The arrangement of the Hop domains in the complex seems to prevent total closure of the Hsp90 dimer, thus blocking ATPase activity and generating a semiclosed conformation that allows client protein binding 16,27,28 .…”
Section: Discussionsupporting
confidence: 90%
“…This domain is located in the Hsp90 monomer, opposite the monomer that interacts with the Hop TPR2A-TPR2B-DP2 module; this supports the idea of asymmetric interaction of the Hsp90 dimer with other chaperones and cochaperones 14,16,27 . Once the interaction between Hsp70 and Hop takes place, there appears to be a further interaction between Hsp70 NBD and the Hsp90-N on one Hsp90 monomer, which Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Initially, we found that Hsp90 was predominantly dimeric and FKBP52 monomeric, both were anticipated. Recently there has been some controversy over the oligomeric state of Hop reported as dimeric (6,20,34) or monomeric (22,35) and Hsp70 can form high oligomeric species under some conditions (36). We have shown that under the conditions used here both proteins are monomeric.…”
Section: Discussionmentioning
confidence: 64%
“…stress-induced phosphoprotein 1; Hsp70-Hsp90 organizing protein; Hop; STI1; p60) is a cochaperone protein that has been implicated with protein folding. 42 Stip1 has been indirectly implicated in b-cells. Pdx1 is known to occupy a site near Stip1.…”
Section: Discussionmentioning
confidence: 99%